Novel CT-based classification of Hoffa fracture and optimal treatment strategies - Chen, Haiming; He, Mingwei; Li, Guodong; Wang, Jinqiu; Yang, Kaimin; Wei, Qingjun (Frontiers in Surgery, 2025)
BackgroundThe imaging characteristics of Hoffa fracture are gradually changing, leading to limitations of the existing classification system and necessitating the development of a novel classification system to guide clinical management.ObjectiveThis study proposes a novel classification method for Hoffa fracture through a retrospective analysis of CT imaging characteristics, biomechanical studies, and case reports and suggests corresponding surgical approaches and internal fixation methods.MethodThe CT imaging characteristics of 115 adults with Hoffa fractures from five tertiary hospitals were analyzed, accompanied by a retrospective review of biomechanical studies and case reports, to propose a novel classification system. Corresponding surgical approaches and internal fixation methods were recommended. Six independent observers evaluated the inter- and intra-observer reliability of the novel classification system.ResultsThe new classification method includes four broad types, and the recommended surgical approach and fixation strategy for each type have been identified. The mean Kappa coefficients for the first and second rounds of inter-observer were 0.766 and 0.752, respectively, with a mean Kappa coefficient for intra-observer of 0.853.ConclusionThe proposed classification system aligns closely with the clinical characteristics of Hoffa fracture, facilitates the differentiation of various fracture types, and recommends appropriate surgical approaches and fixation methods. This classification method also presents good inter- and intra-observer reliability and can be used in clinical management.